2023
DOI: 10.3390/healthcare11040482
|View full text |Cite
|
Sign up to set email alerts
|

Swimmers with Down Syndrome Are Healthier and Physically Fit than Their Untrained Peers

Abstract: While there are positive benefits from physical activity participation for individuals with Down syndrome, little is known about the effects of swimming training. The aim of this study was to compare the body composition and physical fitness profile of competitive swimmers and moderately active (untrained) individuals with Down syndrome. The Eurofit Special test was applied to a group of competitive swimmers (n = 18) and a group of untrained individuals (n = 19), all with Down syndrome. In addition, measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…This was also confirmed by the study of Herrera-Quintana et al [ 35 ], but a 2-year follow-up examination indicated a similar tendency for an increase in indicators of body build such as BMI and WHR and decrease in lean mass and bone mass in both genders [ 35 ]. On the contrary, the study conducted by Querido et al [ 37 ] reported a similar prevalence of changes in the body build and posture in both males and females with DS. The inconsistencies in the results of the abovementioned research can be explained mainly by differences in the characteristics of participants presented in the qualitative analysis of this systematic review i.e., (1) internal compensatory mechanisms induced by the internal variables such as (a) level of ID, (b) gender, (c) age, (d) intrinsic characteristics of the morpho-functional development, (e) body mass, (f) ligament laxity and joints mobility, and (2) external mechanisms induced by the following external variables i.e., (a) type of sport, (b) training load (years of training/ number of training sessions per week), and (c) footwear.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This was also confirmed by the study of Herrera-Quintana et al [ 35 ], but a 2-year follow-up examination indicated a similar tendency for an increase in indicators of body build such as BMI and WHR and decrease in lean mass and bone mass in both genders [ 35 ]. On the contrary, the study conducted by Querido et al [ 37 ] reported a similar prevalence of changes in the body build and posture in both males and females with DS. The inconsistencies in the results of the abovementioned research can be explained mainly by differences in the characteristics of participants presented in the qualitative analysis of this systematic review i.e., (1) internal compensatory mechanisms induced by the internal variables such as (a) level of ID, (b) gender, (c) age, (d) intrinsic characteristics of the morpho-functional development, (e) body mass, (f) ligament laxity and joints mobility, and (2) external mechanisms induced by the following external variables i.e., (a) type of sport, (b) training load (years of training/ number of training sessions per week), and (c) footwear.…”
Section: Discussionmentioning
confidence: 76%
“…Both LM and bone mass were found to decrease and BMI, FM, and WHR were found to increase with age in both genders ( p <0.05). Querido et al [ 37 ] nP=37 females and males (DS swimmers) nP=18; nF=4; nM=14/age=22.2±5.4 (DS untrained subjects) nP=19; nF=10; nM=9/age=26.6±8.2 Assessment of the body composition of DS competitive swimmers and untrained DS subjects Harpender skinfold caliper Electronic weighing scale) SG1 vs. SG2 44.4% vs.52.6% - incidence of overweight/obese 51.5±16.5 vs. 81.9±27.9 – skinfold sum 25.4±3.8 vs. 30.7±10.2 – BMI 21.2±6.0 vs. 29.8±7.1 - % BF 22.1±4.2 vs. 20.05±3.7 – lean BM 9.3±3.5 vs. 13.6±6.1 – FM index Characteristics of the body posture – feet Pau et al [ 25 ] nP=118 females and males (Male, obese DS individuals – SG1) nP=34/age=12.3±2.7 (Female, obese DS individuals – SG2) nP=25/age=12.7±2.7 (Male, DS individuals with normal body mass– CG1) nP=34/age=12.8±2.7 (Female, DS individuals with normal body mass– CG2) nP=25/age=12.3±3.1 Characterization of the effect of obesity on foot-ground contact in young DS individuals during quiet upright stance Pressure-sensitive mat (Tekscan Inc, South Boston, MA) In both male and female DS children, flatfoot was found to be the predominant arch type that simultaneously was not related to obesity. Obesity was found to impact on the foot-ground interaction, which was higher in female DS children (larger contact areas and higher plantar pressure in the fore/midfoot).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential mechanism for increasing muscle strength in Down syndrome may be due to the occurrence of regular and programmed muscle contractions that lead to adaptation of the body which is characterized by an increase in muscle strength. Increased physical exercise has been linked to improved muscular strength in people with Down syndrome [31,32]. Due to their restricted cognitive capacities, people with Down syndrome have special requirements and problems that make them exposed to risk factors in the obesogenic environment [33].…”
Section: Discussionmentioning
confidence: 99%
“…The body composition and physical restriction profiles of competitive swimmers and moderately active (detrained) individuals with Down's syndrome were compared. The results indicated that competitive swimming had a positive effect on reducing the tendency toward obesity and improving the strength, efficiency, and balance of this population [17].…”
mentioning
confidence: 90%